2022
DOI: 10.1007/s11127-022-01006-z
|View full text |Cite
|
Sign up to set email alerts
|

Inframarginal externalities: COVID-19, vaccines, and universal mandates

Abstract: COVID-19 vaccine mandates are in place or being debated across the world. Standard neoclassical economics argues that the marginal social benefit from vaccination exceeds the marginal private benefit; everyone vaccinated against a given infectious disease protects others by not transmitting the disease. Consequently, private levels of vaccination will be lower than the socially optimal levels due to free-riding, which requires mandates to overcome the problem. We argue that universal mandates based on free-rid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Addressing the problems presented by the COVID-19 pandemic, researchers in liberal political economy have challenged the supposed trade-off between protection against infectious disease and economic freedom (Furton, 2023 ; Geloso et al, 2021 ; Geloso & Murtazashvili, 2021 ; Koyama, 2023 ), shown that political incentives encourage officials to adopt stricter measures than is economically efficient (Allen, 2022 ; Boettke & Powell, 2021 ; Hebert & Curry, 2022 ; Leeson & Thompson, 2023 ; Murtazashvili and Zhou this volume ; cf. Garzarelli et al, 2022 ), including measures that persist after the danger has passed (Goodman et al, 2021 ), proposed that spontaneous endogenous citizen responses to novel infections are more effective than typically predicted (Allen et al, 2022 ; Leeson & Rouanet, 2021 ), and highlighted how decisions in the private sector can internalise many of the relevant externalities associated with the infection (Albrecht & Rajagopalan, 2023 ). Paniagua and Rayamajhee challenge the presumption that the global scale of the pandemic means that national and international policy intervention are where any possible solution lies (Paniagua & Rayamajhee, 2022 ; Rayamajhee and Paniagua 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the problems presented by the COVID-19 pandemic, researchers in liberal political economy have challenged the supposed trade-off between protection against infectious disease and economic freedom (Furton, 2023 ; Geloso et al, 2021 ; Geloso & Murtazashvili, 2021 ; Koyama, 2023 ), shown that political incentives encourage officials to adopt stricter measures than is economically efficient (Allen, 2022 ; Boettke & Powell, 2021 ; Hebert & Curry, 2022 ; Leeson & Thompson, 2023 ; Murtazashvili and Zhou this volume ; cf. Garzarelli et al, 2022 ), including measures that persist after the danger has passed (Goodman et al, 2021 ), proposed that spontaneous endogenous citizen responses to novel infections are more effective than typically predicted (Allen et al, 2022 ; Leeson & Rouanet, 2021 ), and highlighted how decisions in the private sector can internalise many of the relevant externalities associated with the infection (Albrecht & Rajagopalan, 2023 ). Paniagua and Rayamajhee challenge the presumption that the global scale of the pandemic means that national and international policy intervention are where any possible solution lies (Paniagua & Rayamajhee, 2022 ; Rayamajhee and Paniagua 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ancak burada ortaya çıkan sorun, ücretsiz aşı olanların sağladığı pozitif dışsallıktan aşı olmayanların bedavacılık yoluyla faydalanmasıdır. Diğer bir teşvik örneği de aşı fiyatlarının negatif olması yani aşı olanlara devletin ödeme yapmasıdır (Albrecht & Rajagopalan, 2022).…”
Section: Introductionunclassified
“…Similarly, Albrecht and Rajagopalan ( 2022 ) question the economic rationale behind COVID-19 vaccine mandates. Like most vaccines, COVID-19 vaccines protect individuals against the most severe symptoms of the virus.…”
mentioning
confidence: 99%